2010
DOI: 10.1111/j.1708-8240.2010.00318.x
|View full text |Cite
|
Sign up to set email alerts
|

Irradiance Uniformity and Distribution from Dental Light Curing Units

Abstract: Using different light guides on the same LCU significantly affected the power output, irradiance values, and beam homogeneity. For all LCUs, irradiance values calculated using conventional methods (I(CM)) did not represent the irradiance distribution across the tip end of the LCU. CLINICAL SIGNIFICANCE Irradiance values calculated using conventional methods assume power uniformity within the beam and do not validly characterize the distribution of the irradiance delivered from dental light curing units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 24 publications
(81 reference statements)
0
53
0
3
Order By: Relevance
“…Care should be taken again because a 40-second exposure time is usually twice the time indicated for most of the resin composites available in the market, and very low radiant exposures could be delivered by some LCUs in shorter photoactivation times. In addition, it has been reported that the irradiance delivered from LCUs is not uniform across the light tip, 22 which may also hinder calculation of energy doses applied to the restorative materials. The light spectral emission of the LEDs tested was usually centered on the 450-to 470-nm range, with narrower emission distribution compared with the QTH unit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Care should be taken again because a 40-second exposure time is usually twice the time indicated for most of the resin composites available in the market, and very low radiant exposures could be delivered by some LCUs in shorter photoactivation times. In addition, it has been reported that the irradiance delivered from LCUs is not uniform across the light tip, 22 which may also hinder calculation of energy doses applied to the restorative materials. The light spectral emission of the LEDs tested was usually centered on the 450-to 470-nm range, with narrower emission distribution compared with the QTH unit.…”
Section: Discussionmentioning
confidence: 99%
“…Development of the polymerization reaction is influenced by many factors related to the composite, such as comonomer formulation, [1][2][3][4] shade, 5 translucency, 6 and filler loading/size, 7 as well as to the curing unit, such as irradiance level, [8][9][10] exposure time, 11,12 emission spectrum, 13 and thermal variation. 14,15 Sufficient light energy reaching the composite is necessary to ensure adequate polymerization; the spectral irradiance of the light also has to overlap as much as possible the absorption spectrum of the photosensitizer contained in the material, that is, camphorquinone (CQ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, substrate PMMA, dimension of cavity preparation (and volume of restorative material), type of composite, the distance and positioning of light tip, and type of light curing unit were all standardized. It is known that most curing units do not emit homogeneous light, resulting in different degree of conversion values at the composite surface and subsurface 36,37) . Variations on distance from the light tip and irradiance could modify volumetric shrinkage using the same material 7,22,38) .…”
Section: Discussionmentioning
confidence: 99%
“…Attempting to polymerize the sample with single-point lightcuring, the tip of the light-curing device was positioned 10 mm from the sample in the present study. A reduction of approximately 75% in the energy density when the tip is positioned at 10 mm from the sample has been reported (PRICE, et al 2011). This significant reduction in the energy density reduces the polymerization of resin cement and its mechanical properties, explaining the lowest values observed when only one point was used to light-cure the samples (HALVORSON, et al 2002;BAEK, et al 2008;GRITSCH, et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the light beams emitted by device tip are divergent, the diameter of light over the samples tends to increase with longer distances from the tip PRICE, 2003). However, increasing the distance between the tip and sample also reduces the energy density (PRICE, et al 2011). Attempting to polymerize the sample with single-point lightcuring, the tip of the light-curing device was positioned 10 mm from the sample in the present study.…”
Section: Discussionmentioning
confidence: 99%